RESILIENSI KAWASAN HERITAGE MELALUI ADAPTIVE REUSE BERBASIS ARSITEKTUR REGENERATIF (STUDI KASUS: REVITALISASI STASIUN SEMUT SURABAYA UNTUK PENGUATAN INTERKONEKSI RUANG KOTA) (Jurnal Arsitektur ARCADE, 2026)
Surabaya’s Semut Station is a colonial architectural artifact suffering from dual degradation: internal physical deterioration and external spatial isolation. This study aims to formulate a design framework for adaptive reuse based on regenerative architecture in the Semut Station area as a strategy to strengthen the interconnectivity of urban spaces in North Surabaya. The approach used is descriptive qualitative, employing data collection techniques through field observations and in-depth interviews with key stakeholders, including passengers, vendors, PT KAI management, and government officials. The analysis encompasses an area assessment (urban grain, transportation network), spatial and environmental analysis (sun-wind, microclimate), mapping of the area’s value ecosystem. The research results indicate that a regenerative adaptive reuse approach can transform heritage buildings from a critical condition (resilience score of 32.5) to a good condition (projected score of 78.75) through three main programs: Heritage Zone (transportation museum, colonial gallery), Living Transit Hub (TOD integration & mobility interconnectivity), Ecological Public Space (green systems, SMEs, co-working). Unlike the dominant static conservation paradigm in Indonesia, this approach positions historic buildings as active living systems urban acupuncture nodes that stimulate multidimensional regeneration of the area. This research contributes to an integrative and sustainable theoretical and practical model for urban heritage transformation.